Integrative proteomic and lipidomic analysis of GNB1 and SCARB2 knockdown in human subcutaneous adipocytes - Takuya Kitamoto; Aya Kitamoto (PLoS ONE, 2025)
Obesity, a global public health concern, is influenced by various factors, including genetic predispositions. Although many obesity-associated genes have been identified through genome-wide association studies (GWAS), the molecular mechanisms linking these genes to adipose tissue function remain largely unexplored. This study integrates proteomic data on adipocyte fat accumulation with GWAS data on obesity to unravel the roles of the identified key candidate genes — G protein subunit beta 1 (GNB1) and scavenger receptor class B member 2 (SCARB2) — involved in fat accumulation. We utilized RNA interference to knock down GNB1 and SCARB2 in human subcutaneous adipocytes, followed by lipidome and proteome analyses using mass spectrometry. Knockdown of these genes resulted in a reduction in lipid droplet accumulation, indicating their role in adipocyte lipid storage. Digital PCR confirmed effective gene knockdown, with GNB1 and SCARB2 mRNA levels significantly reduced. In total, the lipidomic analysis identified 96 lipid species with significant alterations. GNB1 knockdown resulted in a decrease in cholesterol esters and an increase in phosphatidylcholines, phosphatidylinositols, and ceramides. SCARB2 knockdown also led to an increase in phosphatidylcholines, with a trend towards decreased triacylglycerols. Proteomic analysis revealed significant changes in proteins involved in lipid metabolism and adipocyte function, including PLPP1 and CDH13, which were upregulated following GNB1 knockdown, and HSPA8, which was downregulated. Conversely, SCARB2 knockdown resulted in the downregulation of PLPP1 and METTL7A, and the upregulation of PLIN2, HSPA8, NPC2, and SQSTM1. Our findings highlight the significant roles of GNB1 and SCARB2 in lipid metabolism and adipocyte function, providing insights that could inform therapeutic strategies targeting these regulatory genes in obesity.